Clementi’s “Progressive Sonatinas,” Op. 36: Sonata semplice or Mediating Genre between Minuet and Sonata Design? - Jurkowski, Edward (Intersections, 2010)
In this article, I apply William E. Caplin’s theoretical model of formal functions as the modus operandi to study variations to the sonatina genre. In particular, I use Clementi’s op. 36 cycle of six “Progressive” sonatinas to illustrate some of the compositional options available along the evolutionary pathway between a single-themed minuet exposition and that of a mature sonata exposition. Despite the sonatina’s relatively smaller dimension, the variety of loosening features and use of interthematic fusion reveal that the genre is a more captivating topic of study than may have been generally appreciated.